2015
DOI: 10.1161/circresaha.116.304944
|View full text |Cite|
|
Sign up to set email alerts
|

Coronary Neutrophil Extracellular Trap Burden and Deoxyribonuclease Activity in ST-Elevation Acute Coronary Syndrome Are Predictors of ST-Segment Resolution and Infarct Size

Abstract: Rationale: Mechanisms of coronary occlusion in ST-elevation acute coronary syndrome are poorly understood. We have previously reported that neutrophil (polymorphonuclear cells [PMNs]) accumulation in culprit lesion site (CLS) thrombus is a predictor of cardiovascular outcomes. Objective: The goal of this study was to characterize PMN activation at the CLS. We examined the relationships between CLS neutrophil extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
406
0
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(435 citation statements)
references
References 44 publications
18
406
0
11
Order By: Relevance
“…The importance of these findings is underscored by the detection of NET in association with neutrophils in specimens of human coronary thrombi ( Figure 1) and at lesion sites of patients with acute myocardial infarction and stent thrombosis. 6,53,54 NET could only be detected in early stages of coronary thrombosis, but not in organized thrombi, which could be attributed to digestion of NET by plasma DNases or disruption of NET by heparin treatment applied during cardiac catheterization. 53 Increased NET burden in coronary thrombi correlated with infarct size, and DNase treatment (in particular together with tissue plasminogen activator) promoted resolution of coronary thrombi ex vivo, suggesting that a combination of established antithrombotic and NET-disrupting therapy might be beneficial in the therapy of acute coronary syndromes.…”
Section: Detection and Functional Role Of Neutrophil Extracellular Trmentioning
confidence: 96%
See 2 more Smart Citations
“…The importance of these findings is underscored by the detection of NET in association with neutrophils in specimens of human coronary thrombi ( Figure 1) and at lesion sites of patients with acute myocardial infarction and stent thrombosis. 6,53,54 NET could only be detected in early stages of coronary thrombosis, but not in organized thrombi, which could be attributed to digestion of NET by plasma DNases or disruption of NET by heparin treatment applied during cardiac catheterization. 53 Increased NET burden in coronary thrombi correlated with infarct size, and DNase treatment (in particular together with tissue plasminogen activator) promoted resolution of coronary thrombi ex vivo, suggesting that a combination of established antithrombotic and NET-disrupting therapy might be beneficial in the therapy of acute coronary syndromes.…”
Section: Detection and Functional Role Of Neutrophil Extracellular Trmentioning
confidence: 96%
“…5 In parallel, it was shown that NET derived from neutrophils are present at sites of pathological thrombus formation in large arteries in experimental mouse models as well as in coronary thrombi of patients. 6 Notably, a substantial fraction of neutrophilderived extracellular nucleosomes did not exhibit the typical morphology of NET and were present in fragmented forms.…”
Section: Propagation Of Thrombosis By Neutrophils and Extracellular Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is no consensus about the clinical significance of NETosis in diabetes beyond early atherosclerosis and CV complications (Freigang et al, 2013;Mangold et al, 2014). Although chronic lowgrading microvascular inflammation is considered a clue in the pathogenesis of atherosclerosis, the factors that trigger and sustain the inflammation remain elusive.…”
Section: Clinical Relevance Of Spon-taneous / Inducible Netosis In DImentioning
confidence: 99%
“…Unfortunately, there is no consensus about the clinical significance of NETosis in diabetes beyond early atherosclerosis and CV complications [27,28]. Although chronic low-grading microvascular inflammation is considered a clue in the pathogenesis of atherosclerosis, the factors that trigger and sustain the inflammation remain elusive.…”
Section: Clinical Relevance Of Spontaneous/inducible Netosis In Diabementioning
confidence: 99%